Classification Poverty Levels in Indonesia Using Discriminant Analysis - Muthahharah, Isma; Hafid, Hardianti (Jurusan Matematika FMIPA UNM, 2025)
Poverty is a complex global challenge affecting countries like Indonesia that seek to improve the welfare of their citizens. Although the number of Indonesia's poor has fluctuated over the past few years, the study shows a decline in 2022. Using Multivariate Discriminant Analysis, this study aims to classify poverty levels in Indonesian provinces. Previous findings highlighted the relationship between the poverty depth index and average and duration of schooling. Through the development of classification models, this research seeks to provide a better understanding of poverty factors and support more effective policymaking in combating poverty in various regions. Using secondary data from the Central Bureau of Statistics in 2022, this research is quantitative research that produces important insights for the formulation of poverty eradication policies and programs in Indonesia. The result is the low provincial group of 20 provinces only 10 provinces are correctly predicted, the remaining 10 are predicted in the high province group. The same thing happened in the high province group of 13 provinces, only 9 provinces were correctly predicted, while the remaining 4 were predicted in the low group.